Campaign Finance Reform, Free Speech and the Supreme Court - Langhauser, Derek (Maine Policy Review, 2003)
In December 2003, the United States Supreme Court upheld all the key provisions of the Bipartisan Campaign Finance Reform Act (BCRA) of 2002. In their 5-4 decision, the justices deferred broadly to the limitations set by Congress on unregulated “soft money” and “issue ads” in political campaigns. Derek Langhauser, who worked in Senator Olympia Snow’s office as counsel in McConnell v FEC, as this case was called, gives a legal history of the challenge of balancing Congress’ interest in protecting the integrity of elections with the Constitution’s competitive rights of free speech and association. He describes in detail the Supreme Court’s decision, the implications of the decision, and the role of the Court in representative democracy.